Distinguishing two morphologically similar species of Asteraceae using a chloroplast DNA marker - Susanto, Agus Hery; Dwiati, M (Proceeding ICMA-SURE; Vol 1 No 1 (2021): Proceeding ICMA-SUREDO - 10.20884/2.procicma.2021.1.1.4423, 2021)
Synedrella nodiflora (L.) Gaertn and Calyptocarpus vialis Less are members of Asteraceae family that morphologically show high similarities. To genetically distinguish between them, a particular molecular marker should be employed. This study aims to present molecular comparison between both species using a chloroplast DNA marker, i.e. atp B – rbc L IGS. A pair of PCR universal primers was used to amplify the marker. Sequence alignment on the PCR products reveals longer S. nodiflora sequence in comparison to that of C. vialis . In addition, some transversions and transitions are also observed. This suggests that the two species exhibit considerable genetic difference despite t heir similar phenotypic appearance